Case Report: The Imperfect Association Between Craniofacial Lesion Burden and Pain in Fibrous Dysplasia - Golden, Emma; Zhang, Fan; Selen, Daryl J.; Ebb, David; Romo, Laura; Drubach, Laura A.; Shah, Nehal; O'Donnell, Lauren J.; Lemme, Jordan D.; Myers, Rachel; Cay, Mariesa; Kronenberg, Henry M.; et al. (Frontiers in Neurology, 2022)
Patients with fibrous dysplasia (FD) often present with craniofacial lesions that affect the trigeminal nerve system. Debilitating pain, headache, and migraine are frequently experienced by FD patients with poor prognosis, while some individuals with similar bone lesions are asymptomatic. The clinical and biological factors that contribute to the etiopathogenesis of pain in craniofacial FD are largely unknown. We present two adult females with comparable craniofacial FD lesion size and location, as measured by 18F-sodium fluoride positron emission tomography/computed tomography (PET/CT), yet their respective pain phenotypes differed significantly. Over four weeks, the average pain reported by Patient A was 0.4/0-10 scale. Patient B reported average pain of 7.8/0-10 scale distributed across the entire skull and left facial region. Patient B did not experience pain relief from analgesics or more aggressive treatments (denosumab). In both patients, evaluation of trigeminal nerve divisions (V1, V2, and V3) with CT and magnetic resonance imaging (MRI) revealed nerve compression and displacement with more involvement of the left trigeminal branches relative to the right. First-time employment of diffusion MRI and tractography suggested reduced apparent fiber density within the cisternal segment of the trigeminal nerve, particularly for Patient B and in the left hemisphere. These cases highlight heterogeneous clinical presentation and neurobiological properties in craniofacial FD and also, the disconnect between peripheral pathology and pain severity. We hypothesize that a detailed phenotypic characterization of patients that incorporates an advanced imaging approaches probing the trigeminal system may provide enhanced insights into the variable experiences with pain in craniofacial FD